Manajemen Wisata Religi Dalam Meningkatkan Daya Tarik Terhadap Makam Mbah Zakaria di Desa Rowolaku: Religious Tourism Management in Increasing the Attractiveness of Mbah Zakaria's Tomb in Rowolaku Village - Larassanti, Eno; Zaenab, Zaenab; Darmaningrum, Khaerunnisa Tri (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research originated from the author's curiosity about the state and condition of Mbah Zakaria's Tomb and the Conditions of Tourist Attractions under the leadership of the Mbah Zakaria Dining Board, Rowolaku Village, Kajen District, Pekalongan Regency. Furthermore, the author conducted research by trying to go directly to the field or the destination of the survey was the burial place of Mbah Zakaria to meet the guard as the caretaker of Mbah Zakaria's tomb. This research is qualitative research. The author's method used in this study is the inductive method. The inductive method is a way of discussing a problem that is different from existing and real information and facts, from conclusions then more general conclusions are drawn. In this case, the author's approach refers to the science of da'wah, this study approach Using one of these auxiliary sciences is a management approach. To obtain the necessary information, the author uses a method of data collection, participant observation, interviews and documentation. The purpose of this study is to find out the application and functions of these. Management of Religious Tourism of Mbah Zakaria's Tomb in Rowolaku Village, Kajen District, Pekalongan Regency. Referring to the existing theory of control functions, although not optimally applied, namely: planning, organization, activation (movement) and control (tracking).